2019
DOI: 10.1021/acs.jpcc.9b06927
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of CO and H2 on an Iron Surface and Its Implication on the Hydrogen Embrittlement of Iron

Abstract: We investigated the competitive coadsorption of carbon monoxide and hydrogen gas on an iron surface with a 110 facet using density functional theory. Our study discusses the hydrogen dissociation reaction on a fresh iron surface and a surface with varying carbon monoxide coverage. Additionally, we investigated the carbon monoxide surface adsorption as a function of the carbon monoxide surface coverage. Our results show different trends for the carbon monoxide adsorption and hydrogen dissociation on surfaces wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The CO mitigation effect on the HEE in a fracture toughness test was reduced with a decrease in the loading rate. [17] The hydrogen gas pressure dependence on the mitigation effect of CO on the susceptibility to HEE observed in this study can also be ascribed to the same mechanism. This consideration is the case where a new fresh Fe surface is continuously created by crack extension during the fracture toughness test after the CO coverage reaches the maximum value.…”
Section: B Theoretical Consideration By Molecular Dynamics Simulationsupporting
confidence: 64%
See 4 more Smart Citations
“…The CO mitigation effect on the HEE in a fracture toughness test was reduced with a decrease in the loading rate. [17] The hydrogen gas pressure dependence on the mitigation effect of CO on the susceptibility to HEE observed in this study can also be ascribed to the same mechanism. This consideration is the case where a new fresh Fe surface is continuously created by crack extension during the fracture toughness test after the CO coverage reaches the maximum value.…”
Section: B Theoretical Consideration By Molecular Dynamics Simulationsupporting
confidence: 64%
“…The coadsorption of H 2 and CO on the Fe surface has recently been investigated in detail using first principle calculations. [17] The results showed that CO surface coverage is crucial for understanding the mitigation effect of CO impurities in H 2 gas on the susceptibility to HEE. The maximum CO coverage on the Fe surface was estimated to be limited to approximately 75 pct.…”
Section: B Theoretical Consideration By Molecular Dynamics Simulationmentioning
confidence: 96%
See 3 more Smart Citations